2021
DOI: 10.3847/1538-3881/abca8d
|View full text |Cite
|
Sign up to set email alerts
|

The K2 M67 Study: Precise Mass for a Turnoff Star in the Old Open Cluster M67

Abstract: We present a study of the bright detached eclipsing main-sequence binary WOCS 11028 (Sanders 617) in the open cluster M67. Although the binary has only one eclipse per orbital cycle, we show that the masses of the stars can be derived very precisely thanks to a strong constraint on the orbital inclination: M A  = 1.222 ± 0.006M ⊙ and M B  = 0.909 ± 0.004M ⊙. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 107 publications
2
6
0
Order By: Relevance
“…about 8σ lower). We confirm that we also get the same result with the new version of parsec and leave this problem to a more exhaustive investigation using new parsec models with varying initial metallicity and He content (see also Sandquist et al 2021).…”
supporting
confidence: 80%
See 1 more Smart Citation
“…about 8σ lower). We confirm that we also get the same result with the new version of parsec and leave this problem to a more exhaustive investigation using new parsec models with varying initial metallicity and He content (see also Sandquist et al 2021).…”
supporting
confidence: 80%
“…Recently, it has been shown that M67 harbours an interesting spectroscopic binary system located near the turnoff region, WOCS 11028, that challenges theoretical models (see Sandquist et al 2021, for a thorough discussion). Briefly, the mass of the primary component is estimated to be M WOCSa = 1.222 ± 0.006 M , while current predictions using different stellar evolution codes (including parsec V1.2S) give values that are lower by δ m = 0.05 M (i.e.…”
mentioning
confidence: 99%
“…about 8σ lower. We confirm that we get the same result also with the new version of parsec and leave this problem to a more exhaustive investigation using new parsec models at varying initial metallicity and He content (see also Sandquist et al 2021).…”
supporting
confidence: 80%
“…3. The ages of the clusters used to calibrate the gyrochronology themselves have significant standard errors and systematics; full consideration of these is beyond the scope of this work but should be included when considering rotation-based ages in an absolute sense (Sandquist et al 2021).…”
Section: Gyrochrone Errormentioning
confidence: 99%